Economic Downturns, Retirement and Long-Term Cognitive Function Among Older Americans - Hessel, Philipp (J Gerontol B Psychol Sci Soc Sci, 2018)
OBJECTIVE: Workers approaching retirement may be particularly vulnerable to economic downturns. This study assesses whether exposure to economic downturns around retirement age leads to poorer cognitive function in later life. METHOD: Longitudinal data for 13,577 individuals in the Health and Retirement Study were linked to unemployment rates in state of residence. Random- and fixed-effect models were used to examine whether downturns at 55–64 years of age were associated with cognitive functioning levels and decline at ≥65 years, measured by the Wechsler Adult Intelligence Scale-Revised. RESULTS: Longer exposure to downturns at 55–64 years of age was associated with lower levels of cognitive function at ≥65 years. Compared to individuals experiencing only up to 1 year in a downturn at 55–64 years of age, individuals experiencing two downturns at these ages had 0.09 point (95% Confidence Interval [CI, −0.17, −0.02]) lower cognitive functioning scores at ≥65 years (3 years: b = −0.17, 95%CI [−0.29, −0.06]; 4 years: b = −0.14, 95%CI [−0.25, −0.02]; ≥5 years: b = −0.22, 95%CI [−0.38, −0.06]). Downturns at 55–64 years of age were not associated with rates of cognitive decline. DISCUSSION: Exposure to downturns around retirement is associated with a long-lasting decline in cognitive function in later life. Policies mitigating the impact of downturns on older workers may help to maintain cognitive function in later life.